2014
DOI: 10.1172/jci71389
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes expressing CX3CR1 orchestrate the development of vincristine-induced pain

Abstract: A major dose-limiting side effect associated with cancer-treating antineoplastic drugs is the development of neuropathic pain, which is not readily relieved by available analgesics. A better understanding of the mechanisms that underlie pain generation has potential to provide targets for prophylactic management of chemotherapy pain. Here, we delineate a pathway for pain that is induced by the chemotherapeutic drug vincristine sulfate (VCR). In a murine model of chemotherapy-induced allodynia, VCR treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(199 citation statements)
references
References 53 publications
8
185
1
Order By: Relevance
“…The trafficking of different types of leukocytes in the PNS and CNS has distinct temporal profiles; the initial trafficking of neutrophils (hours) is followed by trafficking of macrophages (days) and then infiltration of T cells (days to weeks) 28, 29 . In particular, neuroinflammation manifests as activation of glial cells, such as Schwann cells in the nerve, satellite glial cells in the ganglia and microglia, and astrocytes and oligodendrocytes in the spinal cord and brain 30 .…”
Section: Neuroinflammationmentioning
confidence: 99%
“…The trafficking of different types of leukocytes in the PNS and CNS has distinct temporal profiles; the initial trafficking of neutrophils (hours) is followed by trafficking of macrophages (days) and then infiltration of T cells (days to weeks) 28, 29 . In particular, neuroinflammation manifests as activation of glial cells, such as Schwann cells in the nerve, satellite glial cells in the ganglia and microglia, and astrocytes and oligodendrocytes in the spinal cord and brain 30 .…”
Section: Neuroinflammationmentioning
confidence: 99%
“…36 In addition, Elizabeth reported that CX3CL1/CX3R1 signal in the sciatic nerve participated in the vincristine-induced painful peripheral neuropathy. 11 These research suggested that CX3CL1 in the peripheral nervous system might be a critical molecular in chemotherapeutic drug-induced peripheral neuropathy. In the current study, our data first revealed that paclitaxel treatment also increase the expression of CX3CL1 in dorsal horn neurons.…”
Section: Pain Medicinementioning
confidence: 99%
“…Recently, our and peer's studies showed that CX3CL1-induced peripheral axonopathy and ganglionopathy is involved in painful neuropathy after chemotherapeutic drug treatment. 10,11 Although it has been well documented that the CX3CL1/ CX3CR1 signaling regulates the interaction between neuronal-microglia in the spinal cord and thereby mediates the development of neuropathic pain, 6,12 involvement of ABSTRACT Background: Up-regulation of CX3CL1 has been revealed to be involved in the neuropathic pain induced by nerve injury. However, whether CX3CL1 participates in the paclitaxel-induced painful peripheral neuropathy remains unknown.…”
mentioning
confidence: 99%
“…Recent reports suggest that other chemokines also significantly participate in neuropathic pain in the PNS and CNS (56,67,68). In the PNS, CCL3 (macrophage inflammatory protein-1α; MIP-1α) (69), CCL4 (MIP-1b) (70), CCL5 (regulated upon activation, normal T-cell expressed and secreted; RANTES) (71), CXCL2 (growth-related oncogene b; GROb) (72,73), and CX 3 CL1 (fractalkine) (74) were identified as key mediators of neuropathic pain. These chemokines substantially facilitate the development of peripheral sensitization and mediate neuropathic pain through the recruitment of leukocytes and the cytokine-chemokine network (53,67).…”
Section: Other Chemokines Involved In Neuropathic Painmentioning
confidence: 99%